Representasi Makna Rumah dan Pencarian Jati Diri Dalam Film “Ku Kira Kau Rumah” - Arneta Febrianti, Liliana; Anisa Dwi Rohmatin; Aghata Prahista Pramuditya; Muh Fahrel Nu Ceha; Liliana Ameta Febrianti (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2025)
AbstractThis study examines the representation of the meaning of home and its relation to the search for identity in the film Kukira Kau Rumah. Home is not only understood as a physical place, but also an emotional and psychological symbol that influences individuals in finding their identity. The purpose of this study is to analyze the representation of the meaning of home in the film Kukira Kau Rumah as a symbol of the search for identity using Roland Barthes' semiotic approach. This study uses a qualitative descriptive method with Roland Barthes' semiotic analysis. The main instrument is the observation of the film text through scene and dialogue analysis, as well as data recording. This data analysis technique uses an interactive analysis model that involves data collection, reduction, presentation, and drawing conclusions. The results of this study indicate that the film Kukira Kau Rumah represents the meaning of home as a symbol that is deeper than just a physical building. The house in this film actually becomes a symbol of limitationsBarthes, pressure, and emotional conflict experienced by the main character, Niskala.